The Flow of Money Demand in Indonesia: What Drives it? - Wijaya, Adi; Nurjanana, Nurjanana; A, Erwin Kurniawan (Asian Journal of Economic Modelling, 2022)
Indonesia’s economy is experiencing a contemporary phase marked by decades of financial turmoil. Fluctuations in money demand are inseparable from the responsibilities of Bank Indonesia, which is the holder of rules and regulations and has full control of tracking the effects of financial flows. In reality, the imbalance between the demand for money and the supply of money with limited stock and capacity has an impact on macroeconomic turmoil. The orientation of this study follows up on the causality between gross domestic product (GDP), deposit interest rates and the rupiah exchange rate against the demand for money in Indonesia. The quantitative research approach supports the objective. Time series data from 2006–2020 was obtained from the Central Statistics Agency of Indonesia and Bank Indonesia. The data was analyzed using the error correction model (ECM) through EViews 9.0. The indications are that in the short and long terms, GDP and the rupiah exchange rate have a positive effect and increase the demand for money. An increase in deposit rates has a negative effect on the demand for money. Holistic recommendations concentrate on parallel and collaborative monetary instruments between executive parties, including banking. Also, it is necessary to control and visualize policies that are more comprehensive and consider holistic issues related to the aggressiveness of money circulation, which has the potential to disrupt the macroeconomy.